Artbin: Extended sample size for randomized trials with binary outcomes. (March 2023) - Marley-Zagar, Ella; White, Ian R.; Royston, Patrick; Barthel, Friederike M.-S.; Parmar, Mahesh K. B.; Babiker, Abdel G.
We describe the commandartbin, which offers various new facilities for the calculation of sample size for binary outcome variables that are not otherwise available in Stata. Whileartbin has been available since 2004, it has not been previously described in the Stata Journal .artbin has been recently updated to include new options for different statistical tests, methods and study designs, improved syntax, and better handling of noninferiority trials. In this article, we describe the updated version ofartbin and detail the various formulas used withinartbin in different settings.